PENGARUH FREE CASH FLOW, OWNERSHIP STRUCTURE, GROWTH OPPORTUNITY DAN PROFTABILITAS TERHADAP KEBIJAKAN DEVIDEN - Lia Susanah; Nova Adhitya Ananda (Jurnal Ekonomi dan Bisnis Indonesia, 2022)
This study aims to examine the effect of Free Cash Flow, Owner Ship Structure, Growth opportunity, and Profitability on Dividend Policy. The sampling technique used was purposive sampling, namely sampling with certain criteria set by the researcher. The analytical tool used in this study is Panel Data Multiple Linear Regression. The results of this study indicate that Free Cash Flow has a positive and not significant effect on dividend policy, the owner ship structure has a positive and not significant effect on dividend policy, return on assets has a positive and insignificant effect on dividend policy, and Growth opportunity has a positive and insignificant effect on dividend policy.